Alternative for Dirty Cooking Fuels in Ghana: Exploring the Potential of Cassava Ethanol - Adu, Theophilus Frimpong; Lamptey, Francis Padi; Kaburi, Sandra Ama; Otoo, Gifty Serwaa (Review of Energy Technologies and Policy Research, 2022)
Fossil fuels are a major contributor to climate change, and as the demand for energy production increases, alternative sources (e.g., renewables) are becoming more attractive. Kerosene and conventional solid fuels, which are used to cook, have detrimental effects on people's health, the environment, and the economy. This study seeks to explore the potential of cassava ethanol as an alternative to dirty cooking fuels in Ghana. The study revealed that the prices of electricity and liquefied petroleum gas (LPG) are on the rise and this is making their adoption very low. The use of ethanol, an alternative clean cooking fuel that can be produced locally and reasonably priced, should be encouraged. Cassava was selected as the most viable crop for ethanol production because it is highly underutilized and can be grown on most Ghanaian land. The study also revealed that the Crop Research Institute-Agra (CRI-Agra) Bankye, a variety of cassava, will give an optimum ethanol yield. It has the potential to produce one litre of ethanol from about 7kg of fresh roots. Approximately 147 Ha of agricultural land may be used to produce 1 ton of cassava ethanol. Since cassava ethanol for cooking offers major potential for climate change mitigation, there should be an adoption strategy. This work serves as input for decision-making for industrializing the cassava sector.